2023
DOI: 10.1155/2023/8891070
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pesticides on Diversity and Abundance of Predatory Arthropods in Rice Ecosystem

A. M. Raut,
A. Najitha Banu,
Waseem Akram
et al.

Abstract: Rice (Oryza sativa) is one of the most important cereal crops with a diverse set of pests and natural enemies. Rice fields often support a high diversity of arthropods which contribute significantly to productivity. This diversity is frequently threatened due to indiscriminate applications of pesticides. Our aim was to emphasize on the predator diversity in agrochemical exposed rice field as well as on the impact of surrounding vegetation on beneficial insect diversity. Natural enemies’ data were recorded from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…The BIPM treatments have a more even distribution of species as compared to FP 1, FP 2 and UC (Table 4). The studies conducted by Raut et al, (2023) recorded less natural enemy diversity (odonatan and hymenopteran) in plots sprayed with Chlorpyriphos and methyl parathion when compared to unsprayed plots. They also reported that the plots sprayed with Cartap hydrochloride were on par with the unsprayed plots for the diversity of predator population and species evenness supporting the results obtained for FP 1 where need-based application of Cartap hydrochloride was followed (Table 4).…”
Section: Diversity Indices Of Natural Enemy Populationsmentioning
confidence: 98%
“…The BIPM treatments have a more even distribution of species as compared to FP 1, FP 2 and UC (Table 4). The studies conducted by Raut et al, (2023) recorded less natural enemy diversity (odonatan and hymenopteran) in plots sprayed with Chlorpyriphos and methyl parathion when compared to unsprayed plots. They also reported that the plots sprayed with Cartap hydrochloride were on par with the unsprayed plots for the diversity of predator population and species evenness supporting the results obtained for FP 1 where need-based application of Cartap hydrochloride was followed (Table 4).…”
Section: Diversity Indices Of Natural Enemy Populationsmentioning
confidence: 98%